Loanwords in chinese vocabulary (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the methods of formation of loan words in Chinese. The study of loan words in the Chinese language is one of the most important issues in the field of Chinese language teaching. The use of loanwords in Chinese, their classification by meaning and translation in a context, is one of the main problems of the language.
Keywords: transliteration; semantics; morpheme; affix screening